2023
DOI: 10.1371/journal.pone.0292292
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19’s shadow on families: A structural equation model of parental stress, family relationships, and child wellbeing

Antje von Suchodoletz,
Jocelyn Bélanger,
Christopher Bryan
et al.

Abstract: The present study seeks to contribute to developmental science in emergencies by investigating associations between COVID-19 pandemic-related stressors, parents’ stress, family relationships, and child wellbeing. In doing so, we build on recent research that generalizes the assumptions of the Family Stress Model beyond direct economic stressors of households to macro-contextual stressors that operate at the societal level. In the case of our study, these stressors relate to the COVID-19 pandemic, such as healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…It was shown that family structure and family function moderated the relationship between burnout and mental health [15]. An online survey in the United Arab Emirates showed that higher parental stress and lower child well-being were associated with pandemic-related stressors, and family relationship was the mediator [16]. Dayton's work showed that parental caregiving strain was a risk factor associated with child anxiety, and income loss was associated with sleep disturbances [17].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that family structure and family function moderated the relationship between burnout and mental health [15]. An online survey in the United Arab Emirates showed that higher parental stress and lower child well-being were associated with pandemic-related stressors, and family relationship was the mediator [16]. Dayton's work showed that parental caregiving strain was a risk factor associated with child anxiety, and income loss was associated with sleep disturbances [17].…”
Section: Introductionmentioning
confidence: 99%